(untitled) (Journal of Bangladesh Academy of Sciences, 2022)
Lifetimes of the upper states of excited oxygen atoms corresponding to transitions to the common lower state in the case of the emission lines around 777 nm and 844 nm have been estimated by measuring the line intensities as a function of the delay time between the Q-switching of the laser and the opening of the window of the ICCD. In the case of the emission line around 777 nm, resulting from the transitions from the three very closely spaced upper energy levels, 2s2 2p3 (4S0) 3p5P3 (777.194 nm), 2s2 2p3 (4S0) 3p5P2 (777.417 nm) and 2s2 2p3 (4S0) 3p5P1 (777.539 nm) to the common lower energy level 2s2 2p3 (4S0) 3s5S2, the lifetime was measured to be 253 ns. Similarly, in the case of the emission-line around 844 nm, resulting from the transitions from the three very closely spaced upper energy levels 2s2 2p3 (4S0) 3p3P0 (844.625 nm), 2s2 2p3 (4S0) 3p3P2 (844.636 nm) and 2s2 2p3 (4S0) 3p3P1 (844.676 nm) to the common lower energy level 2p3 (4S0) 3s3S1, the lifetime was measured to be 278 ns by this technique. The measured lifetimes in our experiment, for both 777 nm and 844 nm atomic transition lines of oxygen (O), are almost nine times higher than the theoretical value. Self-absorption and radiation trapping are possible mechanisms responsible for the mismatch between measured and intrinsic lifetimes. Last but not least, utilizing the TR-LIBS technique is yet another incredible application to estimate the prolonged lifetime of closely spaced excited states of an atom in the presence of self-absorption and radiation trapping. The average plasma cooling temperature (excitation temperature) lifetime was found to be 1183 ns, which is compatible with the previously reported values. J. Bangladesh Acad. Sci. 46(2); 175-183: December 2022